J.M. Coetzee and the christian tradition: navigating religious legacies in the novel - Broggi, A (2017)
This thesis examines how J.M. Coetzee's engagement with Christian thinkers and concepts has shaped his fiction. Through a series of close readings, I show how Coetzee, who does not identify as a Christian, reworks and reimagines concepts from key Christian interlocutors across his writings. Each close reading is informed by a consideration of what Coetzee had himself been reading during the writing process, based on evidence in interviews, essays, monographs, and archival materials. Attending to Coetzee's reading and writing, together, illuminates the distinctively self-conscious nature of his engagement with Christianity. Whereas current Coetzee criticism has given attention to specific Christian themes and lexical choices in his fiction, this thesis demonstrates that Coetzee's engagement with Christianity is more profound and pervasive than has been credited hitherto. In addition to the vast body of allusion to Scripture in his writings, Christian thinkers have in fact played a major role in his innovative approach to the novel, a genre predominantly forged in Christian contexts, and in his handling of narrative more generally. Through its explication of Coetzee's extensive dialogue with Christian thinking, and with the Bible, across the full span of his career, this thesis seeks to describe the nuanced and diverse ways in which Coetzee's writings have revised and reimagined this vast and complex religious legacy.